Spontaneous Calcium Oscillations through Differentiation: A Calcium Imaging Analysis of Rat Cochlear Nucleus Neural Stem Cells - Johannes Voelker; Christine Voelker; Jonas Engert; Nikolas Goemann; Rudolf Hagen; Kristen Rak (Cells, 2021)
Causal therapies for the auditory-pathway and inner-ear diseases are still not yet available for clinical application. Regenerative medicine approaches are discussed and examined as possible therapy options. Neural stem cells could play a role in the regeneration of the auditory pathway. In recent years, neural stem and progenitor cells have been identified in the cochlear nucleus, the second nucleus of the auditory pathway. The current investigation aimed to analyze cell maturation concerning cellular calcium activity. Cochlear nuclei from PND9 CD rats were microscopically dissected and propagated as neurospheres in free-floating cultures in stem-cell medium (Neurobasal, B27, GlutaMAX, EGF, bFGF). After 30 days, the dissociation and plating of these cells took place under withdrawal of the growth factors and the addition of retinoic acid, which induces neural cell differentiation. Calcium imaging analysis with BAPTA-1/Oregon Green was carried out at different times during the differentiation phase. In addition, the influence of different voltage-dependent calcium channels was analyzed through the targeted application of inhibitors of the L-, N-, R- and T-type calcium channels. For this purpose, comparative examinations were performed on CN NSCs, and primary CN neurons. As the cells differentiated, a significant increase in spontaneous neuronal calcium activity was demonstrated. In the differentiation stage, specific frequencies of the spontaneous calcium oscillations were measured in different regions of the individual cells. Initially, the highest frequency of spontaneous calcium oscillations was ascertainable in the maturing somata. Over time, these were overtaken by calcium oscillations in the axons and dendrites. Additionally, in the area of the growth cones, an increasing activity was determined. By inhibiting voltage-dependent calcium channels, their expression and function in the differentiation process were confirmed. A comparable pattern of maturation of these channels was found in CN NSCs and primary CN neurons. The present results show that neural stem cells of the rat cochlear nucleus differentiated not only morphologically but also functionally. Spontaneous calcium activities are of great relevance in terms of neurogenesis and integration into existing neuronal structures. These functional aspects of neurogenesis within the auditory pathway could serve as future targets for the exogenous control of neuronal regeneration.